Pengaruh model pembelajaran inkuiri terhadap hasil belajar matematika kelas V sekolah dasar - Muhammad Asro; Sri Utaminingsih; Fitri Budi Suryani (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of the research was to analyze the effect of the inquiry model on mathematics learning outcomes in fifth grade elementary school students, Wedung District, Demak Regency. Data collection techniques through tests, observations, interviews and documentation. The population in this study were all 5th grade students of SD Wedung District, Demak Regency, totaling 167 students, with the research sample being class V SDN Kenduren 1 as the control class and SDN Buko as the experimental class. Data analysis is normality test, homogeneity test, t test and n-gain test. The result of this research is that there is a significant effect of the Inquiry learning model on the learning outcomes of mathematicians in the fifth grade elementary school students in Wedung District, Demak Regency because tcount > ttable (6.166 > 2.0049)